2013
DOI: 10.1088/0960-1317/23/3/035030
|View full text |Cite
|
Sign up to set email alerts
|

Replication of nano/micro-scale features using bulk metallic glass mold prepared by femtosecond laser and imprint processes

Abstract: This study describes the replication of nano/micro-scale features using a Pd 40 Ni 40 P 20 bulk metallic glass (BMG) mold prepared using a femtosecond laser and nanoimprinting process. The use of the beam shaper feature of the femtosecond laser enabled the rapid fabrication of periodic nanostripes over an area of ∼5 × 4 mm 2 on the BMG mold following a single pulse of irradiation. The ablation pitch of the nanostructure irradiated with 100 mW of femtosecond laser power was determined to be 175.8 nm. The imprin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…In the area of multiple pulse micromachining of BMGs, it is also of interest to mention two studies that reported the application of laser processing as one possible step in a process chain to fabricate micro-components. These include the work of Chen et al (2013), who demonstrated the machining of periodic micro and nano-structures on a Pd-and Ni-based BMG using a fs laser and also, the work of Vella et al (2015). These latter authors described the successful application of ps and ns laser processing to produce patterns in a Vitreloy 1b BMG workpiece, which was subsequently used as a mould for the replication of micro-structured polymer components.…”
Section: Introductionmentioning
confidence: 99%
“…In the area of multiple pulse micromachining of BMGs, it is also of interest to mention two studies that reported the application of laser processing as one possible step in a process chain to fabricate micro-components. These include the work of Chen et al (2013), who demonstrated the machining of periodic micro and nano-structures on a Pd-and Ni-based BMG using a fs laser and also, the work of Vella et al (2015). These latter authors described the successful application of ps and ns laser processing to produce patterns in a Vitreloy 1b BMG workpiece, which was subsequently used as a mould for the replication of micro-structured polymer components.…”
Section: Introductionmentioning
confidence: 99%
“…After optimizing the process parameters, this method achieved precise fabrication of micro/nano channels at low cost. Chen et al studied a bulk metallic glass (BMG) stamp to replicate micro/nanoscale features ranging from 90 nm to 100 μm [ 9 ]. Their work ensures that BMG stamps, which are suitable for MEMS applications, can transfer micro-/nanoscale patterns.…”
Section: Introductionmentioning
confidence: 99%
“…The ubiquitous alternative route of using elastomeric replicas as a flexible transfer method for micro/nanoembossing 18 is incompatible with forming nanostructures in highly viscous (10 6 -10 9 Pa-s) BMG melts due to mechanical collapse of the nanostructures on the replica, although the resulting deformation in such structures on the microscale was recently exploited to generate multiscale macro/microstructured BMGs 19 . In fact, the only replica material that has successfully been utilized to nanopattern BMGs is a higher temperature BMG 6,20 . Excluding any issues with the master, forming against a multiscale BMG replica would mechanically bond the two rigid structures upon cooling, making their separation impossible without damage.…”
Section: Introductionmentioning
confidence: 99%